Large-eddy simulation of a pulsed jet into a supersonic crossflow. (25th November 2016) - Shi, Haitao; Wang, Guolei; Luo, Xisheng; Yang, Jiming; Lu, Xi-Yun
Highlights: Flow mechanism of a pulsed jet into a supersonic crossflow has been studied by LES. Pulsed jet can increase the jet penetration and improve the jet mixing. Pulsed jet can induce large-scale jet shear vortices and complex shock structures. Forcing pulsation takes over the primary frequency of flow field in the jet control. Intensive turbulent fluctuations are formed by the interaction of shocks/vortices. Abstract: Numerical investigation of a pulsed jet injected into a supersonic crossflow was carried out using large-eddy simulation. The corresponding steady jet injection was also calculated for comparison with the pulsed jet injection and for validation against experimental data. Various fundamental mechanisms dictating the intricate flow characteristics, such as multi-scale vortical structures, complex shock systems, mixing properties and turbulence behaviors, have been studied. As the pulsed jet issuing transversely into the supersonic crossflow, the salient shock systems and vortical structures in terms of the instantaneous and phase-averaged flow field are analyzed. The large-scale jet shear vortices are formed along the interface of jet and crossflow due to the pulsation effect, which can promote the engulfing of the crossflow fluid and the mixing of the jet and crossflow fluids. Further we investigate turbulence properties of the jet and crossflow interaction and scalar statistics of the injectant mass fraction to reveal jet penetration enhancement and mixing property improvement for the pulsed jet. Results obtained in this study provide physical insight into the understanding the mechanisms for the interaction of pulsed jet and supersonic crossflow.